Pengaruh Pemberian Percutaneus Electrical Stimulation Terhadap Lingkar Pinggang Pada Penderita Obesitas Sentral (Di Lingkungan Akademi Akupunktur Surabaya) - Wahyuni, Dyah Prapti; Endaryanto, Agung Hadi; Priasmoro, Dian Pitaloka; Abdullah, Ahmad - (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2022)
Objective: This study aims to prove Dry Needling Percutaneus Electrical Stimulation has an effect to reduce waist circumferrence in central obesity patient.Â Methods: The design of this study is Pra-Experimental with one group pre test-post test design. The study was conducted in August to September 2021. Given ten treatments with the number of sample of used twenty respondens taken from the results of pre-test and post-test that fit the inclution criteria of this study. Â Results: Measurements of waist circumferrence with measuring tape. Using the Wilcoxone Signed Rank-Test and obtained the result PË‚0,05. Conclusion: Based on the result of the statistical tests it can be concluded that Dry Needling Percutaneus Electrical Stimulation has an effect on reducing waist circumferrence patient at the area of Academy Acupuncture of Surabaya.